Transformasi Digital dan Dampaknya terhadap Kompetensi Sumber Daya Manusia di Era Industri 5.0 - Nugroho, Wijil; Tambunan, Leo Alexander (LPPM Institut Pendidikan Nusantara Global, 2025)
The era of Industry 5.0 marks a new phase in technological advancement, emphasizing human-centered innovation and collaboration through the integration of artificial intelligence, automation, and humanistic values. This study aims to: (1) analyze the characteristics of digital transformation relevant to both domestic and global contexts; (2) identify the competencies required by human resources (HR) to effectively adapt to digital work environments; and (3) formulate strategies and frameworks for the sustainable development and evaluation of digital-based HR competencies. A descriptive qualitative approach was employed, using data collection techniques such as literature review, limited qualitative surveys, and in-depth interviews with informants from the education, industry, and government sectors. Data analysis was conducted using a thematic approach to identify conceptual patterns aligned with the research objectives. The findings reveal that digital transformation drives changes in organizational work structures, making them more flexible, collaborative, and adaptive. It also demands competencies from HR that are not only technical (such as digital literacy, data management, and digital platform utilization) but also adaptive (such as critical thinking, virtual communication, self-directed learning, and digital ethics). Effective HR competency development strategies must be holistic, sustainable, and impact-driven, encompassing digital competency mapping, implementation of blended learning, career pathway integration, and data-driven performance evaluation. This study contributes to the development of both conceptual and practical models for building a human resource ecosystem capable of navigating the digital transformation in the Industry 5.0 era.